2011
DOI: 10.1152/ajpgi.00177.2011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of parietal cell superoxide dismutase leads to gastric oxidative stress and increased injury susceptibility in mice

Abstract: Jones MK, Zhu E, Sarino EV, Padilla OR, Takahashi T, Shimizu T, Shirasawa T. Loss of parietal cell superoxide dismutase leads to gastric oxidative stress and increased injury susceptibility in mice. Am J Physiol Gastrointest Liver Physiol 301: G537-G546, 2011. First published June 30, 2011 doi:10.1152/ajpgi.00177.2011Mitochondrial superoxide dismutase (SOD2) prevents accumulation of the superoxide that arises as a consequence of oxidative phosphorylation. However, SOD2 is a target of oxidative/nitrosative ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The accumulation of ROS triggers the p38 MAPK -p16 INK4a /p19 ARF signaling pathway selectively in parietal cells and the consequent induction of parietal cell loss. In fact, parietal cells have been reported to contain abundant mitochondria (32), a major source of intrinsic ROS production, and have been considered to be highly susceptible to oxidative stress (33). Together, oxidative stressdependent p38…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ROS triggers the p38 MAPK -p16 INK4a /p19 ARF signaling pathway selectively in parietal cells and the consequent induction of parietal cell loss. In fact, parietal cells have been reported to contain abundant mitochondria (32), a major source of intrinsic ROS production, and have been considered to be highly susceptible to oxidative stress (33). Together, oxidative stressdependent p38…”
Section: Discussionmentioning
confidence: 99%
“…( 5 ) Thus, reflux of gastric luminal acid into the esophageal lumen readily causes esophageal mucosal injury, manifested clinically as reflux esophagitis. It has been reported that H + not only injures epithelial cells, but also causes free radical generation in their mitochondria, ( 6 8 ) exacerbating acid-induced injury and inflammation. ( 9 ) This suggests that free radicals generated by luminal H + contribute to the pathophysiology of reflux esophagitis.…”
Section: Gi Disorders Caused By Oxidative Stressmentioning
confidence: 99%
“…Bioenergetic studies on the gastric epithelium are relatively limited, especially with respect to investigating human stomach diseases and the use of compound biomarkers [8,10,11,[20][21][22][23][24][25][26][27][28][29][30] . The main purpose of this study was to examine the suitability of using biochemical parameters (cellular respiration, ATP, GSH, and caspase activity) as biomarkers for the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergetics of the gastric epithelium was investigated in specimens collected from animal and human tissues [8,10,11,20] . In the bullfrog gastric mucosa, cellular mitochondrial O2 consumption was increased and cellular ATP was decreased in the presence of acetylsalicylic acid [8] .…”
Section: Discussionmentioning
confidence: 99%